IMPACTS ON CLIMATE CHANGE ON TRIBAL ECONOMY: A STUDY OF JHARKHAND STATE OF INDIA (Proceedings of the International Conference on Poverty and Sustainable Development, 2019)
Climate change has become a major issue of concern during recent years. It has affected the life, livelihood and economy of the tribal people and threatened their survival. There are about 700 different tribes in India as per the Article 342 of the Constitution of India. According to the census 2011, tribal population consisted 8.6 per cent in India. In Jharkhand tribal population represented 24.80 per cent as per census 2011. The huge emission of Green House Gases and decline in forest coverage has resulted into the climate change. The excess emission of the Green House Gases increases the earth’s surface temperature and causes global warming. It has caused discomfort for the tribal people, increased their cost of living and threat for survival, decline in crop production, increase in the incidence of crop diseases, livestock, human beings, social stress and conflict on sharing resources. It is believed that present state of climate change is human induced. In recent years the evidence of climate change is visible in Jharkhand State also. The incidence of drought has increased in entire state. The tribals are mainly dependent on natural resources and rain-fed agriculture. Therefore, they have been adversely affected due to changes in the climatic condition. In this study and attempt is made to find out the changes in climatic condition, assess its negative effects on the tribal economy and livelihood insecurity, evaluate the existing coping mechanism and practices including indigenous methods adopted by the tribals for dealing with the adverse consequences of the changing climate and find out the deficiencies in their traditional coping mechanism and practices in contrast to contemporary scientific approaches and recommend policy to set action plans for the adaptation by tribals of Jharkhand for their sustainable development.
Keywords: climate; tribal; Jharkhand; sustainable; development